1984
DOI: 10.1111/j.1525-1594.1984.tb04295.x
|View full text |Cite
|
Sign up to set email alerts
|

Residual Ethylene Oxide in Hollow‐Fiber Dialyzers

Abstract: The deaeration and extraction kinetics of ethylene oxide (ETO) in hollow-fiber dialyzers were examined. The investigations showed that both deaeration and extraction can be described by two additive first-order kinetic expressions. The ETO content of membranes decreased rapidly at first, followed by a second slower decrease. Even after prolonged storage time, residual ETO was still detectable in the milligram range. These residuals cannot be eliminated by the usual rinsing of the dialyzer prior to use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1985
1985
1989
1989

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…Figure 9 summarizes some of the possible pathways to bioincompatibility which have been suggested from recent studies. Allergic reactions arising from sensitization to ethyl ene oxide are associated with the presence of IgE antibodies against conjugates of human serum albumin and residual ethylene oxide [128,129] present in dialyzer components, especially polyurethane potting materials used with hollow-fiber dialyzers [130], Bind ing of the antigen to IgE antibodies triggers mast cell activation, degranulation and se cretion of a variety of biologically active compounds, including histamine, arachidonic acid metabolites and platelet-activat ing factors.…”
Section: Biocompatibility In Renal Prosthesesmentioning
confidence: 99%
“…Figure 9 summarizes some of the possible pathways to bioincompatibility which have been suggested from recent studies. Allergic reactions arising from sensitization to ethyl ene oxide are associated with the presence of IgE antibodies against conjugates of human serum albumin and residual ethylene oxide [128,129] present in dialyzer components, especially polyurethane potting materials used with hollow-fiber dialyzers [130], Bind ing of the antigen to IgE antibodies triggers mast cell activation, degranulation and se cretion of a variety of biologically active compounds, including histamine, arachidonic acid metabolites and platelet-activat ing factors.…”
Section: Biocompatibility In Renal Prosthesesmentioning
confidence: 99%
“…Others are race, age, the immunological and hormonal status of the host (e.g., histamine releasability), and dose of the sensitogen received. The dose of ETO that dialysis patients are exposed to depends on dialyzer design [e.g., whether or not the dialyzer contains potting compound (18)(19)(20)(21)], the deaeration time of the device, and the rinsing procedure immediately before use.…”
Section: Discussionmentioning
confidence: 99%
“…However, contrary to a previous study [4], there was no clear difference between Ca and PAN equip ment. It may be suggested that this was due to the fact that the PAN filter included in this study was of the hollow-fiber type, hence exposing blood to potting material which can have detrimental effect on biocompatibility [13], but the in vitro incubations ( fig. 7) where only membrane material was used do not support this hypothesis.…”
Section: Discussionmentioning
confidence: 99%